What to Do When Your Municipal Employer Is in Deep Financial Straits: Five Guideposts For Addressing Financial Dysfunction. - GAYDEN, DONNA M. (Public Management (00333611), 2022)
The article reports on municipal financial challenges in the U.S., and offers suggestions for addressing the same. It mentions about hiring an expert team they bring subject matter expertise and objectivity to bolster the case, and establishing a good communication plan in advance for addressing the challanges.